Do Brain Drain and Poverty Result from Coordination Failures? - David de la Croix; Frederic Docquier (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
We explore the complementarities between high-skill emigration and poverty in developing countries. We build a model endogenizing human-capital accumulation, high-skill migration and productivity. Two countries sharing the same characteristics may end up either in a "low poverty/low brain drain" path or in a "high poverty/high brain drain" path. After identifying country-specific parameters, we find that, for a majority of countries, the observed equilibrium has higher income than the other possible one. In 22 developing countries (including 20 small states with less than 2 million inhabitants), poverty and high brain drain are worsened by a coordination failure. For 25 other countries, a radical worsening of economic performances is feasible. These results are fairly robust to identification assumptions and the inclusion of a brain-gain mechanism.
Keywords: F22; F55; D58; D6; D7; 330; Public Good; Inequality Aversion; Immigration policy